Open Sympathectomy Effectiveness on Buerger's Disease’s Pain: An Evidence–Based Case Report - Prawiro, Rangga S.; Utama, Alexander J (The New Ropanasuri Journal of Surgery, 2023)
Introduction. Thromboangiitis obliterans, often referred to as Buerger's disease, is a vascular disease that causes chronic inflammatory conditions, edema, and vascular obstruction due to blood clots. In Cipto Mangunkusumo General Hospital (CMGH), sympathectomy is a rarely done procedure. This evidence–based case report aimed to prove the effectiveness of sympathectomy for Buerger's Disease to reduce pain. Method. We reported a case of 44–year–old male with progressive pain and a history of darkened fingers of left limbs six months before admission. The patient underwent a lumbar sympathectomy, and there was no recurrence of symptoms after one year of follow–up. A systematic literature search proceeded, looking for evidence supporting the effectiveness of such a procedure on some databases and critically appraised. The discussion was elaborated using this evidence. Results. Two eligible articles proceeded with critical appraisal; validity, importance, and applicability were met in these articles. A cohort study from Yazid et al. reported significant improvement in ulcer areas in the intervention and control groups (p Conclusion. The study, supported by high–quality evidence, showed that open sympathectomy surgery effectively reduces the pain in Buerger's disease.